Avaliação da associação da filtração lenta com a filtração rápida no tratamento da água de uma lagoa litorânea tropical com baixa turbidez e cor moderada - Lima, Alexya Brendha Pinheiro de (2019)
Pollution and contamination of water sources are progressively aggravated as urbanization processes and agricultural activities intensify. Water treatment technologies should compensate for this loss of source quality and ensure compliance with the drinking water standard and sanitary safety of treated water, including, among other things, the efficient removal of micro-organisms (including those of emerging concern, such as Giardia and Cryptosporidium), which are difficult to remove in the usual water treatment systems. In this sense, the application of advanced technologies (for example, filter membranes), which, however, are expensive and, therefore, inaccessible to most communities in developing countries. Slow filtration (SF) is a robust treatment technology in relation to pathogen removal, as well as being a technology of affordable cost and easy operation. However, conventional slow filters are ineffective at removing true color. Thus, the main objective of this work is to evaluate the association of conventional slow filtration with rapid filtration (preceded by chemical oxidation and coagulation) for the treatment of the water of a tropical littoral lagoon that presents low turbidity and moderate color. For this, a water source of study (Jiqui Lagoon) was treated: 1) By a pilot installation of SF, composed of two slow sand filters operated in parallel, with constant filtration rate (3 m / day) and varied level, and the granular medium in one of the filters had a coefficient of unevenness of 3 (CU = 3) and in the other, the coefficient of unevenness of 4 (CU = 4); 2) The effluents from the slow filters were treated by pre-oxidation, coagulation and rapid downward filtration in jar test equipment coupled to laboratory filters. The quality of the treated water was evaluated through bacteriological examinations (Total Coliforms and Escherichia coli) and "conventional" physico-chemical analyzes such as turbidity, apparent color, true color and pH, as well as zeta potential analysis. Slow filters, when ripe, achieved the removal of 100% of E. coli and around 98% of Total Coliforms, but did not efficiently remove true color. The slow filter with CU = 4 presented better turbidity removal than with CU = 3. The association of SF with rapid filtration (with pre-oxidation and coagulation) has the potential to achieve high efficiencies in the removal of turbidity, true color and E. coli, reaching values remaining well below the potability standards in force in Brazil, which implies greater sanitary security of treated water.